2021
DOI: 10.1088/2053-1591/ac05fe
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of CO2 adsorption using activated carbon

Abstract: The current study aimed to investigate the CO2 adsorption isotherms of activated carbon (AC), prepared from olive waste via chemical activation by H3PO4. The textural parameters, the microstructural and morphological characterization of the AC were characterized by N2 adsorption-desorption, SEM and XRD. The AC presented the best textural properties with a BET surface area of 1565 m2 g−1 and a micropore volume of 0.649 cm3 g−1. The CO2 adsorption was measured with a volumetric method at three various temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Structural characterization of the AC Figure 1 gives the XRD diffraction of the AC which presents two peaks occurringat 2θ roughly 25°and 42°. These peaks are related to the (001) and (101) planes of the hexagonal structure of graphite [6].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Structural characterization of the AC Figure 1 gives the XRD diffraction of the AC which presents two peaks occurringat 2θ roughly 25°and 42°. These peaks are related to the (001) and (101) planes of the hexagonal structure of graphite [6].…”
Section: Resultsmentioning
confidence: 98%
“…The activated carbon which is utilized in this research is obtained from Tunisian olive waste. [6]. The olive waste has been treated with 85% of phosphoric acid (H 3 PO 4 ) in a weight ratio of 1:1, and the mixture was then heated in an electric oven for 24 h at 100 °C.…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the values displayed in Table 6 , it is observed that the ΔH values were negative for non-modified samples, which confirms an exothermic (physisorption) reaction between the CO 2 and the sorbent [ 22 ], while positive values were obtained for the amine-modified samples, which indicates an endothermic reaction. An endothermic reaction occurs when a large amount of energy is required to desorb an adsorbate (CO 2 ) during a sorption process.…”
Section: Resultsmentioning
confidence: 99%
“…The N 2 gas was passed into the tube furnace for 30 min to replace the air and moisture, after which its temperature was increased to 800 °C at the rate of 2 mL min −1 for 4 h. The cooled char generated was designated as USQ 06_800C, USM 3_800C, USM 5_800C, and US 6_ 800C. Emulating the procedure employed by Almoneef et al [ 22 ], 20 g of each char was added to 60 mL of DETA and EDA separately in conical flasks and stirred continuously in a water shaking bath for 4 h at 70 °C then filtered and washed with 120 mL of methanol. The slurry was finally dried at 80 °C for complete impregnation of the amine functional group to the surface of the samples.…”
Section: Experimentationmentioning
confidence: 99%